The Diagnostic TOEFL Reading Pretest as a Self-Efficacy and Motivational Catalyst in an IndonesianIslamic University EFL Classroom - Wahyu Wahyu; Nirwana Darwis; Dewi Purwati; Nihla Afdaliah; Arifuddin Balla (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
Diagnostic pretests are routinely administered in EFL classrooms yet remain underexplored as motivational and self-efficacy events. This qualitative case study examines how a single pre-instructional TOEFL reading diagnostic pretest shaped the self-efficacy beliefs, motivational orientations, and learning intentions of 32 fourth semester Indonesian EFL students at one of the Islamic universities in Bone Regency, South Sulawesi. Semi structured interview data collected immediately after the pretest but before any formal instruction reveal three consistent patterns: the pretest functioned as a reality check that recalibrated rather than discouraged students; the discovery of specific knowledge and skill gaps through the pretest triggered purposeful rather than avoidant responses; and the encounter produced concrete, student generated learning intentions that students articulated without any instructional prompting. These findings extend self-efficacy theory and assessment for learning frameworks into the Indonesian Islamic EFL context and offer practical implications for the intentional pedagogical use of diagnostic assessment in reading courses.